2016
DOI: 10.1111/jrh.12174
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Abstinence Syndrome in West Virginia Substate Regions, 2007‐2013

Abstract: Purpose The opioid epidemic is a public health threat with consequences affecting newborns. Neonatal Abstinence Syndrome (NAS) is a constellation of withdrawal symptoms resulting primarily from in utero opioid exposure. The purpose of this study is to examine NAS and drug-specific trends in West Virginia (WV), where rurality-related issues are largely present. Methods The 2007–2013 WV Health Care Authority, Uniform Billing Data were analyzed for 119,605 newborn admissions with 1,974 NAS diagnoses. NAS (ICD9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
0
27
2
1
Order By: Relevance
“…16 A study in 2009 showed that 19% of mothers used drugs or drank alcohol during pregnancy in WV. 17 Stabler et al 18 examined the 2007-2013 WV Health Care Authority and Uniform Billing Data for WV and found that between 2007 to 2013 the incidence of NAS increased from 7.74 per 1000 live birth per year to 31.56 per 1000 live birth per year. 18 Most studies use administrative data based on billing and coding from medical documentation to obtain NAS estimates, which leads to a few years of lag in presenting current NAS estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A study in 2009 showed that 19% of mothers used drugs or drank alcohol during pregnancy in WV. 17 Stabler et al 18 examined the 2007-2013 WV Health Care Authority and Uniform Billing Data for WV and found that between 2007 to 2013 the incidence of NAS increased from 7.74 per 1000 live birth per year to 31.56 per 1000 live birth per year. 18 Most studies use administrative data based on billing and coding from medical documentation to obtain NAS estimates, which leads to a few years of lag in presenting current NAS estimates.…”
Section: Introductionmentioning
confidence: 99%
“…17 Stabler et al 18 examined the 2007-2013 WV Health Care Authority and Uniform Billing Data for WV and found that between 2007 to 2013 the incidence of NAS increased from 7.74 per 1000 live birth per year to 31.56 per 1000 live birth per year. 18 Most studies use administrative data based on billing and coding from medical documentation to obtain NAS estimates, which leads to a few years of lag in presenting current NAS estimates. [18][19][20][21] With the steep increase of substance use in the state of WV, this lag may lead to misrepresentation of the current crisis.…”
Section: Introductionmentioning
confidence: 99%
“…7 In a study of 1,974 NAS infants in West Virginia, Stabler et al found that 85% of NAS births were to mothers receiving Medicaid, compared with 54% of non-NAS births. 8 Beyond Appalachia, but still relevant, Lind et al compared characteristics of 242 NAS births to non-NAS births in Florida, finding that NAS births were more likely to be White, low birthweight, and preterm. 9 It is not clear from these and other studies on NAS whether the strikingly higher rates of NAS in the southern Appalachian region can be explained by maternal characteristics unique to this geographic region; it is clear, however, that a better understanding of maternal and infant characteristics and risk factors for NAS is urgently needed.…”
mentioning
confidence: 99%
“…Disproportionate NAS burden in rural communities has been shown nationally and in states like Kentucky and West Virginia . Hospitals in both rural and urban settings should be prepared for longer hospital stays for rural infants with NAS, versus healthy full‐term infants.…”
Section: Discussionmentioning
confidence: 99%
“…Disproportionate NAS burden in rural communities has been shown nationally and in states like Kentucky and West Virginia. 7,46,47 Hospitals in both rural and urban settings should be prepared for longer hospital stays for rural infants with NAS, versus healthy full-term infants. Prior research shows a mean length of stay of 23 days for infants with NAS vs. 2.6 days for healthy infants, with a possible 5-fold increase in neonatal care costs associated with NAS.…”
Section: Discussionmentioning
confidence: 99%